2007
DOI: 10.1002/jqs.1130
|View full text |Cite
|
Sign up to set email alerts
|

Cirque infills in the Khibiny Mountains, Kola Peninsula, Russia — palaeoglaciological interpretations and modern analogues in East Antarctica

Abstract: We report here on cirque infills mapped in the Khibiny Mountains, Kola Peninsula, Russia. Cirque infills are morainic deposits located near the headwalls of valleys and cirques. Their location and shape, often with concave margins towards the valley side, indicate that they were deposited by ice flowing up-valley, into the mountains, rather than by local glaciers. We suggest that they formed during the last deglaciation, when Khibiny was a nunatak and Fennoscandian ice sheet lobes extended into valleys and cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(39 citation statements)
references
References 28 publications
1
38
0
Order By: Relevance
“…However, Jansson and Glasser raised the possibility that pronounced, well-formed ridges in the two cirques referred to above (namely Fan Hir and Cwm Llwch) were formed by a recessional stage of the last ice sheet rather than by small Younger Dryas Stadial age glaciers. This follows recent suggestions of such an origin in, for example, Antarctica, Sweden, and Russia (Hättestrand and Johansen, 2005;Heyman and Hättestrand, 2006;Hättestrand et al, 2008). We categorically disagree with this interpretation.…”
Section: Supposed Ice Sheet Origin Of Valley-head Morainessupporting
confidence: 68%
See 2 more Smart Citations
“…However, Jansson and Glasser raised the possibility that pronounced, well-formed ridges in the two cirques referred to above (namely Fan Hir and Cwm Llwch) were formed by a recessional stage of the last ice sheet rather than by small Younger Dryas Stadial age glaciers. This follows recent suggestions of such an origin in, for example, Antarctica, Sweden, and Russia (Hättestrand and Johansen, 2005;Heyman and Hättestrand, 2006;Hättestrand et al, 2008). We categorically disagree with this interpretation.…”
Section: Supposed Ice Sheet Origin Of Valley-head Morainessupporting
confidence: 68%
“…2B); (v) no erratics were found by Shakesby and Matthews (1993), as would be common if formed by an ice sheet moving across the area (cf. Hättestrand et al, 2008); (vi) it increases in size from the upslope (northern) to downslope (southern) end of the escarpment as would be expected for glacier flow with components of movement both away from the headwall and downslope to the south (cf. Cwm Crew; Fig.…”
Section: Supposed Ice Sheet Origin Of Valley-head Morainesmentioning
confidence: 89%
See 1 more Smart Citation
“…Our interpretation is that these mounds were originally deposited by eastward ice cap retreat and thinning (see below), allowing sediment to accumulate between the ice margin and reverse slope, prior to subsequent ice cap thickening, overriding and streamlining. Hättestrand et al (2008) have reported morphologically similar features, termed 'cirque infills' on the Kola Peninsula in Russia. Abundant sources for the debris would have existed during ice cap thinning and retreat, including: rockfall, fluvial transport from the upper valley, and debris flows / fluvial transport from valley sides and ice margin.…”
Section: Chronologymentioning
confidence: 93%
“…Following deglaciation, mountain landscapes continue to be modified by weathering and erosion (Ballantyne, 2002;Hattestrand et al, 2008). It is important to understand these landscape processes because they may modify the altitudinal range of drainage basins and reduce the gradient of mountainous terrain (Barr & Spagnolo, 2015).…”
Section: Postglacial Erosionmentioning
confidence: 99%